Risk and Crisis Communication in Poultry Agribusiness: A Systematic Literature Review of Disease Outbreak Management and Supply Chain Resilience in Developing Countries - Dita Novarina Gunawati; Cesaria Fitri Puspitasari; Errythrina Vinifera Arnyke; Luky Amalta; Cindy Audina Damayanti (CV. Komunitas Dunia Peternakan, 2026)
Poultry agribusiness is a key driver of food security and rural economic development in developing countries. However, the sector remains vulnerable to infectious diseases such as avian influenza and Newcastle disease, which can disrupt production systems and supply chain continuity. Although previous studies have examined poultry disease control, biosecurity, and supply chain disruption, evidence on how risk and crisis communication supports outbreak management and resilience in developing-country poultry agribusiness remains fragmented. This study applied a systematic literature review (SLR) approach under PRISMA guidelines to synthesize risk and crisis communication strategies in poultry disease management and their contribution to supply chain resilience. Only seven relevant studies published between 2020 and 2025 met the inclusion criteria and were analyzed using the PICO framework. Quality assessment using the Mixed Methods Appraisal Tool (MMAT), combined with systematic data extraction in Microsoft Excel 2021, was conducted to improve methodological transparency and consistency. The novelty of this review lies in integrating communication strategies, enabling and constraining factors, digital tools, One Health perspectives, and public–private collaboration within a single analytical synthesis. The findings indicate that participatory, transparent, and coordinated communication can support disease prevention and crisis preparedness, particularly when strengthened by stakeholder trust, policy support, training, and accessible information channels. However, limited digital literacy, inadequate infrastructure, and cultural barriers may reduce communication effectiveness. Overall, this review highlights the need for inclusive communication systems and collaborative governance to strengthen poultry supply chain resilience in developing countries, while recognizing that the small evidence base limits broad generalization.